Product Market Peers and Relative Performance Evaluation - Jayaraman, Sudarshan; Milbourn, Todd; Peters, Florian; Seo, Hojun (The Accounting Review, 2021)
ABSTRACT We investigate the role of Relative Performance Evaluation (RPE) theory in CEO pay and turnover using a product similarity-based definition of peers (Hoberg and Phillips 2016). RPE predicts that firms filter out common shocks (i.e., those affecting the firm and its peers) while evaluating CEO performance, and that the extent of filtering increases with the number of peers. Despite the intuitive appeal of the theory, previous tests of RPE find weak and inconsistent evidence, which we argue is due to the imprecise categorization of peers. Using product market peers, we find three pieces of evidence consistent with RPE in relation to CEO pay and forced turnover: (1) on average, firms partially filter out common shocks to stock returns, (2) the extent of filtering increases with the number of peers, and (3) firms completely filter out common shocks in the presence of a large number of peers. JEL Classifications: M40; M41; G30; J33.